Talent management to form a rum master (Gestión y Gerencia, 2020)
Companies’ innovation and success depend on people capabilities who work in them. These people must be selected, trained and encouraged to work for the organization; they must share their life purpose with that of the company in a single vision and mission. The research objective is to determine the main characteristics of the master rum makers’ professional profile in Venezuela, through the information analysis gathered from the Internet, such as interviews, corporate information, essays, among others of eight (8) experts. According to the analysis, it could be inferred that for the rum industry, it should be a priority to identify people whose aptitudes and attitudes could be developed towards the formation of a master rum maker. It also became evident that for this type of position within the companies, according to the data analyzed, the right person is a chemical engineer, leader and with the personality of an artist because his work is defined as a passion. In addition, a fundamental part of the training for this role should be framed within the quality area, where basic knowledge is acquired to understand the rum production phenomena. It is concluded that the master rum master training involves years of experience, commitment, as well as sensory, technical and attitudinal skills. It also suggests the need to study in future research the quantitative impact of this position in rum producing organizations.
Keywords: Training; master rum maker; talent management; rum industry